Changes in Pediatric Fracture Cases during the Coronavirus Disease 2019 Pandemic: Data from a National Referral Orthopedic Hospital in Indonesia - Utomo, Pamudji; Wirawan, Muhammad Yogatama; Kumara, Hendra Cahya; Yudistira, Mochamadsyah Beizar (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aims to compare the impact of coronavirus disease 2019 (COVID-19) on pediatric fracture services in a national referral orthopedic hospital in Indonesia to understand the service provisions that may be required during the pandemic. METHODS: The study compared the population group during 1 year of the COVID-19 pandemic in Indonesia to the same period 1 year before. This cross-sectional study was performed in Prof. Dr. R Soeharso Orthopedic Hospital, Surakarta, Indonesia, from March 2019 to February 2021. The subjects were pediatric fracture patients aged 0–18 years. Patients recorded on other orthopedic service support installations such as radiology, laboratory, or physiotherapy and diagnosed with any other orthopedic sub-specialty were excluded. RESULTS: A total of 1787 patients were recorded in this study, with the mean of pediatric fracture patients during the pre-COVID-19 period was 90.75 (standard deviation [SD]: 28.5) and during the COVID-19 period was 58.16 (SD: 19.17) monthly. In the 1st year of the pandemic, there was a significant reduction in clinical visits compared to the same period in 2019 (p < 0.005). CONCLUSION: There were significant differences in pediatric fracture cases clinic visits and patients’ length of stay in the COVID-19 period than before the COVID-19 occurred.